The role of business incubators in supporting startups in Algeria: A case study of the business incubator at the University of Djelfa - Kouider, Ben Bouzid; Abderrahman, Ben Bouzid (International journal of economic perspectives, 2025)
This study aims to introduce business incubators and highlight their role in supporting, developing and protecting startups in Algeria, and because of the importance that algeria attaches to these startups with the aim of achieving economic diversification, which has led to the pursuit and search for ways and mechanisms that would work to provide protection and support for these institutions, The study found that the owners of startups interact positively with the business incubator at the University of Djelfa, because the business incubator at the University of Djelfa contributes to protecting and encouraging these startups, and this was through the use of an opinion poll tool by distributing questionnaire forms to a sample of the owners of startups and Some of the incubator’s employees, extracted the results of the study using the SPSS 25 program.